The Strategy of the Nurul Haramain Putri NW Narmada Islamic Boarding School in Facing the Industrial Era - Erwin Padli; Badrun Badrun; Zaenudin Amrulloh; Baiq Arum Yunita (Potret Pemikiran, 2021)
Entering the industrial era 4.0, the development of professionalization and the increasingly intense competition between lines of life demand an alignment of development orientations to improve human quality. This condition is different from education on the island of Lombok, which is faced with the problem of providing human resources. The mismatch and incompetence between output at all levels of education and social demands in the world of work is an example for educational institutions in Lombok that should be fixed immediately. This study aims to determine the strategy of the Nurul Haramain Islamic Boarding School NW Narmada in preparing graduates who can face the industrial era 4.0. Therefore, Islamic boarding schools, one of the institutions that provide human resources in improving community development and the foundation for non-governmental organizations on the island of Lombok, should improve and formulate new strategies to deal with this. One of them is the Islamic Boarding School of Haramain Putri NW Narmada which is one of the Islamic boarding schools that plays a significant role in preparing human resources for the people of Lombok. This research uses qualitative methods. This method begins with conducting initial observations to the last stage: analyzing and describing the research results. The research found that the Islamic Boarding School of Haramain Putri NW Narmada provided additional hard and soft skill training such as computer refinement and programming, graphic design, language strengthening, and Haramain farming for students. This training is also carried out to prepare graduates who can face changes in the industrial era 4.0.Keywords: Strategy; Islamic Boarding School Nurul Haramain Putri NW Narmada; Industrial Era